Unmet Needs in the Management of Cervical Dystonia - Contarino, Maria Fiorella; Smit, Marenka; van den Dool, Joost; Volkmann, Jens; Tijssen, Marina A. J. (Frontiers in Neurology, 2016)
Cervical dystonia is a movement disorder which affects daily living of many patients. In clinical practice several unmet treatment needs remain open. This article focusses on the four main aspects of treatment. We describe existing and emerging treatment approaches for cervical dystonia, including botulinum toxin injections, surgical therapy, management of non-motor symptoms and rehabilitation strategies. The unsolved issues regarding each of these treatments are identified and discussed, and possible future approaches and research lines are proposed.